Systematic Literature Review: Exploring Research Focus on Ratio and Proportion - Filian Yunita Sari; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Ely Susanti (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2025)
Ratios and proportions are fundamental topics in mathematics education that students must master because they play an important role in the development of mathematical reasoning. The focus of this study is to examine and analyze previous research related to the learning of ratios and proportions in the period 2017–2022 through a Systematic Literature Review (SLR). A total of 19 relevant articles (13 Scopus, 6 Google Scholar) were selected using the Publish or Perish application. The results of the literature review show that students' ability to understand and solve ratio and proportion problems is still relatively low, especially in representing contextual situations in mathematical models, interpreting various representations, relating concepts to real life, and understanding the meaning of formula usage. The results of design research and experimental studies show that learning based on realistic contexts, inquiry approaches, games, and pattern identification strategies can consistently improve students' conceptual understanding and problem-solving abilities. These findings imply the importance of designing ratio and proportion learning that emphasizes active student involvement, the use of contexts that are close to real life, and the strengthening of conceptual understanding. Learning that is oriented towards exploration and conceptual meaning has the potential to be an effective strategy for improving the quality of ratio and proportion learning, especially at the junior high school level.